A konzervativizmus és a liberalizmus Concha Győző gondolkodásában - Vasas, Tamás (Debreceni Jogi Műhely, 2018)
This paper contents the theories of Győző Concha about the scientific interpration of political liberalism and conservatism. In my work i tried to compare the thoughts of the author about the differences and the similarities of these relevant political movements and conceptions.I analised an essay of Concha from the „Hatvan év tudományos mozgalmai között” named compilation.It contents the connecting refers of the antique political philosphy, especially the scientific thinking conception of Aristotle, also the opinion of the authors of the british classsical consevative political thinking, for example Edmund Burke, and i processed the classification of Concha about the scientific work of Gyula Szekfű, named „Három nemzedék.